2021
DOI: 10.18087/cardio.2021.2.n1560
|View full text |Cite
|
Sign up to set email alerts
|

Proactive anti-inflammatory therapy with colchicine in the treatment of advanced stages of new coronavirus infection. The first results of the COLORIT study

Abstract: Actuality The course of the novel coronavirus disease (COVID-19) is unpredictable. It manifests in some cases as increasing inflammation to even the onset of a cytokine storm and irreversible progression of acute respiratory syndrome, which is associated with the risk of death in patients. Thus, proactive anti-inflammatory therapy remains an open serious question in patients with COVID-19 and pneumonia, who still have signs of inflammation on days 7–9 of the disease: elevated C-reactive protein (CRP)>60 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 25 publications
3
47
0
3
Order By: Relevance
“…All studies had used varying definitions of COVID-19 severity. The participants in treatment arms were comparable for the WHO clinical scale, 19 respiratory support, 20 Sequential Organ Failure Assessment Score, 21 National Early Warning Score 2, 24 symptomatic hospital and outpatient clinical score for COVID-19, 24 time from symptom to enrolment. 22 …”
Section: Resultsmentioning
confidence: 99%
“…All studies had used varying definitions of COVID-19 severity. The participants in treatment arms were comparable for the WHO clinical scale, 19 respiratory support, 20 Sequential Organ Failure Assessment Score, 21 National Early Warning Score 2, 24 symptomatic hospital and outpatient clinical score for COVID-19, 24 time from symptom to enrolment. 22 …”
Section: Resultsmentioning
confidence: 99%
“…In this population, the primary endpoint did not reach statistical significance (OR=0.79, 0.61-1.03; p=0.08) (13). Other randomized controlled trials (RCT) and observational studies have also reported benefits for colchicine in COVID-19 (14)(15)(16)(17)(18)(20)(21). To our knowledge, only one prior meta-analysis has been conducted for colchicine in COVID-19 (22).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, they were included in the quantitative analysis (Table 1 ). Three of the studies were randomized controlled trials 3 , 5 , 8 : one was quasi‐experimental, 9 and the remaining were observational. 2 , 6 , 10 , 11 , 12 The only included nonpeer‐reviewed publication by Tardif et al 8 accounted for the majority of included cases (4488 patients) and consisted of nonhospitalized patients.…”
mentioning
confidence: 99%